REPEARTITION: VISUALISASI PERULANGAN PADA KARYA SENI RUPA SEMI-TIGA DIMENSIONAL - Rahim, Muhamad Ali (Universitas Komputer Indonesia, 2021)
In its appreciation, the works form of art created in various and varied forms is always interesting to be listened to and examined. The focus is not merely on what is represented, but also on how to display it. In its development since modern art has shown a variety of displays that are increasingly difficult to categorize. Because various technical developments, mediums, but also the philosophical concepts and ideas of works enable unlimited space for creation. The work with the theme REPEARTITION was designed as a form of response to the phenomenon; the form of the work will focus on the display of repetitive visualization patterns on referential 'objects', both representative and as real objects themselves. In the design an exploration-comparative method for mixed-media is carried out through the use of ready-made objects as